2019
DOI: 10.3390/pathogens8040220
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Epitope Hot Spots of CD4 T Cell Recognition Within Influenza Hemagglutinin During the Primary Response to Infection

Abstract: Antibodies specific for the hemagglutinin (HA) protein of influenza virus are critical for protective immunity to infection. Our studies show that CD4 T cells specific for epitopes derived from HA are the most effective in providing help for the HA-specific B cell responses to infection and vaccination. In this study, we asked whether HA epitopes recognized by CD4 T cells in the primary response to infection are equally distributed across the HA protein or if certain segments are enriched in CD4 T cell epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 86 publications
(145 reference statements)
0
13
0
Order By: Relevance
“…We speculate that the increased CD4 T cell epitope abundance of the HA-ferritin fusion protein constructs may influence the GC B cell response through provision of additional T cell help for cognate B cells. We, and others, have shown that several limited regions within the H1 HA molecule contained the immunodominant CD4 T cell epitopes in both inbred mice and human donors expressing diverse MHC class II alleles 48,63 . Previous studies in pre-clinical animal models indicated that when the antigen-specificity of the T FH repertoire was assessed by AIM assay with HA head and HA stem-derived peptide pools, the HA head was significantly enriched for antigenspecific T FH relative to the HA stem domain 64 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We speculate that the increased CD4 T cell epitope abundance of the HA-ferritin fusion protein constructs may influence the GC B cell response through provision of additional T cell help for cognate B cells. We, and others, have shown that several limited regions within the H1 HA molecule contained the immunodominant CD4 T cell epitopes in both inbred mice and human donors expressing diverse MHC class II alleles 48,63 . Previous studies in pre-clinical animal models indicated that when the antigen-specificity of the T FH repertoire was assessed by AIM assay with HA head and HA stem-derived peptide pools, the HA head was significantly enriched for antigenspecific T FH relative to the HA stem domain 64 .…”
Section: Discussionmentioning
confidence: 81%
“…To determine the epitope specificity of the CD4 T cell response at the level of single peptides, a peptide library of 15-mer peptides overlapping by 11 residues covering the sequence of H. pylori ferritin (Table 1) was used. To test CD4 T cell reactivity directed against HA, we tested an array of major peptide epitopes from A/New/Caledonia/99 HA that had been previously defined by overlapping peptide matrices spanning the full sequence of HA in mouse strains expressing different MHC class II haplotypes (Table 2) [48][49][50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Argentinean scientists showed that vaccination with proteins leads to CD4 T-cells and infection recalls their memory. In addition, the hemagglutinin released by infected or dying cells, rather than infectious virions, is the main source of antigen for antigen presentation after the infection (Knowlden, et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this special issue, Zackery et al ask whether HA epitopes recognized by CD 4 T cells in the primary response to infection are equally distributed across the HA protein. Using mice, their studies revealed that the HA-specific CD 4 T cell epitopes cluster in two distinct regions of HA, which could be important in the development of universal vaccines against influenza [6].…”
mentioning
confidence: 99%